Reactive oxygen species (ROS)-responsive biomaterials for treating myocardial ischemia-reperfusion injury - Zhang, Ying; Jiang, Mantang; Wang, Tao (Frontiers in Bioengineering and Biotechnology, 2024)
Myocardial ischemia-reperfusion injury (MIRI) is a critical issue that arises when restoring blood flow after an ischemic event in the heart. Excessive reactive oxygen species (ROS) production during this process exacerbates cellular damage and impairs cardiac function. Recent therapeutic strategies have focused on leveraging the ROS microenvironment to design targeted drug delivery systems.ROS-responsive biomaterials have emerged as promising candidates, offering enhanced therapeutic efficacy with reduced systemic adverse effects. This review examines the mechanisms of ROS overproduction during myocardial ischemia-reperfusion and summarizes significant advancements in ROS-responsive biomaterials for MIRI treatment. We discuss various chemical strategies to impart ROS sensitivity to these materials, emphasizing ROS-induced solubility switches and degradation mechanisms. Additionally, we highlight various ROS-responsive therapeutic platforms, such as nanoparticles and hydrogels, and their unique advantages in drug delivery for MIRI. Preclinical studies demonstrating the efficacy of these materials in mitigating MIRI in animal models are reviewed, alongside their mechanisms of action and potential clinical implications. We also address the challenges and future prospects of translating these state of the art biomaterial-based therapeutics into clinical practice to improve MIRI management and cardiac outcomes. This review will provide valuable insights for researchers and clinicians working on novel therapeutic strategies for MIRI intervention.